Iridium-containing microcrystalline nanometer material and preparation method and application thereof
By developing iridium-containing microcrystalline nanomaterials, the problem that iridium oxide catalyst in PEMWE cannot operate efficiently and for a long time and stable operation under operating conditions is solved, and the electrocatalytic performance in PEMWE is achieved with high efficiency and long-term stability.
Patent Information
- Application Number
- CN202411794865.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-18
AI Technical Summary
Under the operating conditions of proton exchange membrane water electrolytic cell (PEMWE), the electrochemical properties of iridium oxide (IrO2) catalysts cannot operate efficiently for a long time and stably, resulting in PEMWE losing its market competitiveness.
A nanomaterial containing iridium microcrystals is developed, which consists of iridium elemental crystals and iridium oxide microcrystals (IrOx, 0
The iridium-containing microcrystalline nanomaterial exhibits excellent electrocatalytic activity and long-term stability under the operating conditions of PEMWE, can achieve high current density at a lower voltage, and operate stably for more than 2000 hours at 1A·cm-2, far exceeding the life of commercial catalyst IrO2.
Smart Images

Figure CN119640325A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysis, and specifically relates to an iridium-containing microcrystalline nanomaterial and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane water electrolyzer (PEMWE) has the advantages of high operating current density, high H2 purity and low resistive losses, making it the preferred technology for high efficiency and small footprint. However, the strong acidic and oxidizing environment under PEMWE operating conditions poses substantial challenges to the activity and stability of the catalyst. These challenges are related to the sluggish kinetics of the oxygen evolution reaction (OER) and the dependence on rare key catalysts, such as iridium oxide (IrO2). However, the electrochemical performance of IrO2 is not able to operate efficiently and stably for a long time under the operating conditions of PEMWE, making PEMWE relying on iridium oxide catalysts uncompetitive in the market. Summary of the invention
[0003] In view of this, the object of the present invention is to provide an iridium-containing microcrystalline nanomaterial and a preparation method and application thereof. The iridium-containing microcrystalline nanomaterial not only has excellent electrocatalytic activity, but also has good long-term stability, and can operate efficiently and stably for a long time under the working conditions of PEMWE.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] The present invention provides an iridium-containing microcrystalline nanomaterial, comprising an iridium single substance microcrystalline and an iridium oxide microcrystalline coated on the outer layer of the iridium single substance microcrystalline; the chemical composition of the iridium oxide microcrystalline is IrO x , 0<x<2; has a clustered structure.
[0006] Preferably, the diameter of the iridium-containing microcrystalline nanomaterial is 1 to 2 nm.
[0007] Preferably, the mass percentage of iridium element in the iridium-containing microcrystalline nanomaterial is ≤75%.
[0008] The present invention also provides a method for preparing the iridium-containing microcrystalline nanomaterial described in the above technical solution, comprising the following steps:
[0009] The iridium-containing microcrystalline nanomaterial is obtained by mixing a compound containing iridium ions, an alkali source, a reducing organic alcohol and water and performing a hydrothermal reaction.
[0010] Preferably, the compound containing iridium ions is one or more of iridium chloroacid, iridium tetrachloride and potassium hexachloroiridate (IV).
[0011] Preferably, the alkali source is an alkali metal hydroxide; the alkali metal hydroxide includes one or more of potassium hydroxide, sodium hydroxide, lithium hydroxide and cesium hydroxide.
[0012] Preferably, the reducing organic alcohol is ethylene glycol and / or glycerol.
[0013] Preferably, the temperature of the hydrothermal reaction is 160-220° C., and the insulation time is 12-36 hours.
[0014] The present invention also provides the use of the iridium-containing microcrystalline nanomaterial described in the above technical solution or the iridium-containing microcrystalline nanomaterial prepared by the preparation method described in the above technical solution as a catalyst in a proton exchange membrane water electrolyzer.
[0015] The present invention also provides an anode of a proton exchange membrane water electrolyzer, comprising an anode substrate and an iridium-containing microcrystalline nanomaterial coated on the surface of the anode substrate;
[0016] The iridium-containing microcrystalline nanomaterial is the iridium-containing microcrystalline nanomaterial described in the above technical solution or the iridium-containing microcrystalline nanomaterial prepared by the preparation method described in the above technical solution.
[0017] The present invention provides an iridium-containing microcrystalline nanomaterial, comprising an iridium single substance microcrystalline and an iridium oxide microcrystalline coated on the outer layer of the iridium single substance microcrystalline; the chemical composition of the iridium oxide microcrystalline is IrO x, 0<x<2; has a cluster structure. Compared with the rutile structure of traditional IrO2, the iridium oxide in the iridium-containing microcrystalline nanomaterial provided by the present invention is microcrystalline, with short-range order, long-range disorder, coordination unsaturated environment, isotropic atomic structure and modulated electronic state at the atomic scale. The coordination unsaturated environment means that there are more uncoordinated atoms on the surface of the iridium-containing microcrystalline nanomaterial. These uncoordinated atoms can more easily adsorb reactant molecules, thereby providing more active sites in the catalytic process; the isotropic atomic structure means that the atomic arrangement of the material in different directions is the same, which can provide uniformly distributed active sites. This uniform The uniform distribution reduces the local current density differences that may occur during the reaction, so that the reactants can be uniformly adsorbed and converted, improving the consistency and stability of the electrocatalytic reaction; in the electrocatalytic reaction, the reactant molecules need to be moderately adsorbed on the catalyst surface, and regulating the electronic state can adjust the electron density of the active site, thereby changing the adsorption energy of the reactants, reaction intermediates and products on the surface of the iridium-containing microcrystalline nanomaterial, so that the iridium-containing microcrystalline nanomaterial has a large specific surface area, excellent surface adsorption performance and surface activity, and can expose a high concentration of surface active sites-iridium oxides, thereby improving its electrocatalytic activity. Moreover, during the electrocatalytic process, the iridium single crystals in the iridium-containing microcrystalline nanomaterial can be oxidized to form new iridium oxides, so that it has good long-term stability and can operate efficiently and stably for a long time under the working conditions of PEMWE.
[0018] The results of the examples show that the performance of the iridium-containing microcrystalline nanomaterial provided by the present invention in PEMWE is much higher than that of the commercial catalyst IrO2, reaching 1A·cm under the working conditions of PEMWE (80°C). -2 The current density only needs 1.79V, and it can reach 1A·cm -2 The catalyst can run stably for more than 2000 hours, while the commercial catalyst IrO2 can only run for less than 400 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a transmission electron microscope image of the iridium-containing microcrystalline nanomaterial prepared in Example 1;
[0020] Figure 2 XRD patterns of iridium-containing microcrystalline nanomaterials prepared in Examples 1 to 4;
[0021] Figure 3 The OER polarization curves of the iridium-containing microcrystalline nanomaterials prepared with different alkali sources in Examples 1 to 4;
[0022] Figure 4 The OER polarization curves of the iridium-containing microcrystalline nanomaterial prepared in Example 1 and C-IrO2 in Comparative Example 1;
[0023] Figure 5 This is a polarization curve diagram of the iridium-containing microcrystalline nanomaterial prepared in Example 1 in PEMWE;
[0024] Figure 6 This is a chronopotentiometric curve of the iridium-containing microcrystalline nanomaterial prepared in Example 1 in PEMWE. DETAILED DESCRIPTION
[0025] The present invention provides an iridium-containing microcrystalline nanomaterial, comprising an iridium single substance microcrystalline and an iridium oxide microcrystalline coated on the outer layer of the iridium single substance microcrystalline; the chemical composition of the iridium oxide microcrystalline is IrO x , 0<x<2; has a clustered structure.
[0026] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0027] The iridium-containing microcrystalline nanomaterial provided by the invention comprises iridium single substance microcrystalline and iridium oxide microcrystalline coated on the outer layer of the iridium single substance microcrystalline.
[0028] As an embodiment, the chemical composition of the iridium oxide microcrystals is IrO x , 0<x<2.
[0029] As an implementation manner, the mass percentage of iridium element in the iridium-containing microcrystalline nanomaterial is ≤75%, and in a specific embodiment, it is 74%.
[0030] The mass percentage of the precious metal iridium element in traditional IrO2 is relatively high (85%), which makes the application cost of commercial catalyst IrO2 high. The mass percentage of iridium element in the iridium-containing microcrystalline nanomaterial of the present invention is ≤75%, which reduces the content of iridium element, thereby reducing the cost of using the iridium-containing microcrystalline nanomaterial as a catalyst.
[0031] The iridium-containing microcrystalline nanomaterial provided by the invention has a cluster structure.
[0032] As an implementation mode, the diameter of the iridium-containing microcrystalline nanomaterial is 1 to 2 nm.
[0033] Compared with the rutile structure of traditional IrO2, the iridium oxide in the iridium-containing microcrystalline nanomaterial provided by the present invention is a microcrystalline, which has the characteristics of short-range order, long-range disorder, coordination unsaturated environment, isotropic atomic structure and modulated electronic state at the atomic scale. The coordination unsaturated environment means that there are more uncoordinated atoms on the surface of the iridium-containing microcrystalline nanomaterial, and these uncoordinated atoms can more easily adsorb reactant molecules, thereby providing more active sites in the catalytic process; the isotropic atomic structure means that the atomic arrangement of the material in different directions is the same, which can provide uniformly distributed active sites. This uniform The uniform distribution reduces the local current density differences that may occur during the reaction, so that the reactants can be uniformly adsorbed and converted, improving the consistency and stability of the electrocatalytic reaction; in the electrocatalytic reaction, the reactant molecules need to be moderately adsorbed on the catalyst surface, and regulating the electronic state can adjust the electron density of the active site, thereby changing the adsorption energy of the reactants, reaction intermediates and products on the surface of the iridium-containing microcrystalline nanomaterial, so that the iridium-containing microcrystalline nanomaterial has a large specific surface area, excellent surface adsorption performance and surface activity, and can expose a high concentration of surface active sites-iridium oxides, thereby improving its electrocatalytic activity. Moreover, during the electrocatalytic process, the iridium single crystals in the iridium-containing microcrystalline nanomaterial can be oxidized to form new iridium oxides, so that it has good long-term stability and can operate efficiently and stably for a long time under the working conditions of PEMWE.
[0034] The present invention also provides a method for preparing the iridium-containing microcrystalline nanomaterial described in the above technical solution, comprising the following steps:
[0035] The iridium-containing microcrystalline nanomaterial is obtained by mixing a compound containing iridium ions, an alkali source, a reducing organic alcohol and water and performing a hydrothermal reaction.
[0036] As an embodiment, the iridium ion-containing compound is one or more of iridium chloride (H2IrCl6), iridium tetrachloride (IrCl4) and potassium hexachloroiridate (IV) (K2IrCl6), and in a specific embodiment it is iridium chloride; the alkali source is an alkali metal hydroxide; the alkali metal hydroxide includes one or more of potassium hydroxide (KOH), sodium hydroxide (NaOH), lithium hydroxide (LiOH) and cesium hydroxide (CsOH), and in a specific embodiment it is potassium hydroxide, sodium hydroxide, lithium hydroxide or cesium hydroxide; the reducing organic alcohol is ethylene glycol and / or glycerol, and in a specific embodiment it is ethylene glycol.
[0037] As an embodiment, the mass ratio of the iridium ion-containing compound to the alkali source is 20-80:5-20, and in a specific embodiment, it is 30-50:10-15; the mass ratio of the iridium ion-containing compound to the reducing organic alcohol is 2-8:500-1200, and in a specific embodiment, it is 3-5:565-800; the mass ratio of the iridium ion-containing compound to water is 1-8:500-1500, and in a specific embodiment, it is 2-5:500-1000.
[0038] As an embodiment, the iridium ion-containing compound, the alkali source, the reducing organic alcohol and water are mixed as follows: the iridium ion-containing compound is first dissolved in water, the alkali source is then added for a first stirring, and the reducing organic alcohol is finally added for a second stirring. As an embodiment, the first stirring rate is 3000-5000 rpm, and in a specific embodiment, it is 5000 rpm; the first stirring time is 5-10 min, and in a specific embodiment, it is 5 min; the second stirring rate is 3000-5000 rpm, and in a specific embodiment, it is 5000 rpm; the second stirring time is 20-40 min, and in a specific embodiment, it is 30 min.
[0039] As an embodiment, the equipment used for the hydrothermal reaction is a Teflon-lined stainless steel autoclave.
[0040] As an embodiment, the temperature of the hydrothermal reaction is 160-220° C., and in a specific embodiment, it is 180-200° C., and the insulation time is 12-36 hours, and in a specific embodiment, it is 18-24 hours.
[0041] As an embodiment, after the hydrothermal reaction, the present invention further comprises: cooling the product of the hydrothermal reaction to room temperature, separating the solid from the liquid, and washing and drying the obtained solid in sequence to obtain the iridium-containing microcrystalline nanomaterial.
[0042] As an embodiment, the cooling is natural cooling; the washing is sequentially performed with water and alcohol; the reagent used for the alcohol washing is ethanol; the number of washings is 2 to 5 times, and in a specific embodiment, it is 2 to 3 times; after each washing, it also includes: centrifuging the washed mixed solution; the centrifugal speed is 8000 to 11000 rpm, and in a specific embodiment, it is 9000 to 10000 rpm; the centrifugal time is 5 to 10 minutes, and in a specific embodiment, it is 5 to 8 minutes; the drying is natural drying at room temperature.
[0043] The present invention also provides the use of the iridium-containing microcrystalline nanomaterial described in the above technical solution or the iridium-containing microcrystalline nanomaterial prepared by the preparation method described in the above technical solution as a catalyst in a proton exchange membrane water electrolyzer.
[0044] The present invention has no special limitation on the application of the iridium-containing microcrystalline nanomaterial as a catalyst in a proton exchange membrane water electrolyzer, and any application method known in the art can be used.
[0045] The present invention also provides an anode of a proton exchange membrane water electrolyzer, comprising an anode substrate and an iridium-containing microcrystalline nanomaterial coated on the surface of the anode substrate;
[0046] The iridium-containing microcrystalline nanomaterial is the iridium-containing microcrystalline nanomaterial described in the above technical solution or the iridium-containing microcrystalline nanomaterial prepared by the preparation method described in the above technical solution.
[0047] As an embodiment, the method for preparing the anode of the proton exchange membrane water electrolyzer comprises the following steps: coating the iridium-containing microcrystalline nanomaterial on the surface of the anode substrate.
[0048] The present invention has no special limitation on the anode substrate, and any anode substrate known in the art may be used; the present invention has no special limitation on the coating method and parameters, and any coating method and parameters known in the art may be used.
[0049] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0050] All chemicals used in this invention were obtained from commercial suppliers of analytical grade and used as received without further purification. Iridochloric acid (H2IrCl6), ethylene glycol (EG) and potassium hydroxide (KOH), lithium hydroxide (LiOH), sodium hydroxide (NaOH), cesium hydroxide (CsOH) were purchased from Aladdin.
[0051] Example 1
[0052] 100 mg H2IrCl6 was dispersed in 25 mL water, 30 mg KOH was added, and the mixture was stirred at 5000 rpm for 5 min. Then, 10 mL ethylene glycol (1.13 g / mL) was added and stirred at 5000 rpm for 30 min. The mixture was then transferred to a 50 mL Teflon-lined stainless steel autoclave and subjected to hydrothermal reaction at 180 °C for 24 h. After the mixture was naturally cooled to room temperature, the solid-liquid separation was performed, and the solid was washed with water and ethanol twice each time. After each washing, the solid was centrifuged at 11000 rpm for 5 min and dried naturally at room temperature to obtain iridium-containing microcrystalline nanomaterials (IrO x , 0<x<2, 1~2nm).
[0053] Example 2
[0054] The difference from Example 1 is that KOH is replaced by LiOH.
[0055] Example 3
[0056] The difference from Example 1 is that KOH is replaced by NaOH.
[0057] Example 4
[0058] The difference from Example 1 is that KOH is replaced by CsOH.
[0059] Example 5
[0060] The difference from Example 1 is that ethylene glycol is replaced by glycerol.
[0061] Comparative Example 1
[0062] The commercial catalyst IrO2 (C-IrO2) was used as a comparative example.
[0063] Comparative Example 2
[0064] The difference from Example 1 is that KOH is removed.
[0065] Application Example 1
[0066] The iridium-containing microcrystalline nanomaterial prepared in Example 1 is coated on the anode surface of a proton exchange membrane water electrolyzer to electrolyze water to produce hydrogen.
[0067] Application Examples 2 to 5
[0068] The difference from Application Example 1 is that the iridium-containing microcrystalline nanomaterial prepared in Example 1 is replaced by the iridium-containing microcrystalline nanomaterials prepared in Examples 2 to 5 respectively.
[0069] Comparative application example 1
[0070] The difference from Application Example 1 is that the iridium-containing microcrystalline nanomaterial prepared in Example 1 is replaced by the commercial catalyst IrO2 (C-IrO2) of Comparative Example 1.
[0071] Comparative Application Example 2
[0072] The difference from Application Example 1 is that the iridium-containing microcrystalline nanomaterial prepared in Example 1 is replaced by the catalyst prepared in Comparative Example 2.
[0073] Performance Testing
[0074] (1) Figure 1 This is a transmission electron microscopy image of the iridium-containing microcrystalline nanomaterial prepared in Example 1, where a~b are IrO x SEM image of IrO x HAADF-STEM image of IrO x EDS mapping of Ir and O in the sample, e is IrO xEDSmapping diagram of Ir in, f is IrO x EDS mapping of O in .
[0075] from Figure 1 It can be seen that the IrO prepared by the present invention x The clusters are mainly formed in the form of microcrystals, with an Ir mass fraction of 74%.
[0076] (2) Figure 2 The XRD diagrams of the iridium-containing microcrystalline nanomaterials prepared in Examples 1 to 4 are shown.
[0077] from Figure 2 It can be seen that the iridium-containing microcrystalline nanomaterial prepared by the present invention mainly shows a broad peak without a prominent diffraction peak. x It mainly exists in the form of microcrystals.
[0078] (3) Figure 3 The OER polarization curves of the iridium-containing microcrystalline nanomaterials prepared with different alkali sources in Examples 1 to 4 are shown.
[0079] from Figure 3 It can be seen that the OER performance of iridium-containing microcrystalline nanomaterials prepared with different alkali sources is very good, 10mA·cm -2 The overpotential is 185mV.
[0080] (4) Figure 4 The OER polarization curves of the iridium-containing microcrystalline nanomaterial prepared in Example 1 and C-IrO2 in Comparative Example 1.
[0081] from Figure 4 It can be seen that the IrO prepared by the present invention x The OER performance is much better than that of C-IrO2.
[0082] (5) Figure 5 This is the polarization curve of the iridium-containing microcrystalline nanomaterial prepared in Example 1 in PEMWE.
[0083] from Figure 5 It can be seen that the iridium-containing microcrystalline nanomaterial of the present invention reaches 1A·cm under the working conditions of PEMWE (80°C). -2 The current density only requires 1.79V, enabling operation in PEMWE at a lower voltage.
[0084] (6) Figure 6 This is a chronopotentiometric curve of the iridium-containing microcrystalline nanomaterial prepared in Example 1 in PEMWE.
[0085] from Figure 6It can be seen that under the working conditions of PEMWE (80℃), at 1A·cm -2 The catalyst can run stably for more than 2000 hours, while the commercial catalyst IrO2 can only run for less than 400 hours.
[0086] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An iridium-containing microcrystalline nanomaterial, characterized in that: The invention comprises iridium single substance microcrystals and iridium oxide microcrystals coated on the outer layer of the iridium single substance microcrystals; the chemical composition of the iridium oxide microcrystals is IrO x , 0<x<2; has a clustered structure.
2. The iridium-containing microcrystalline nanomaterial according to claim 1, characterized in that: The diameter of the iridium-containing microcrystalline nanomaterial is 1 to 2 nm.
3. The iridium-containing microcrystalline nanomaterial according to claim 1 or 2, characterized in that: The mass percentage of iridium element in the iridium-containing microcrystalline nanomaterial is ≤75%.
4. The method for preparing the iridium-containing microcrystalline nanomaterial according to any one of claims 1 to 3, characterized in that: The following steps are involved: The iridium-containing microcrystalline nanomaterial is obtained by mixing a compound containing iridium ions, an alkali source, a reducing organic alcohol and water and performing a hydrothermal reaction.
5. The preparation method according to claim 4, characterized in that: The compound containing iridium ions is one or more of iridium chloride, iridium tetrachloride and potassium hexachloroiridate (IV).
6. The preparation method according to claim 4, characterized in that: The alkali source is an alkali metal hydroxide; the alkali metal hydroxide includes one or more of potassium hydroxide, sodium hydroxide, lithium hydroxide and cesium hydroxide.
7. The preparation method according to claim 4, characterized in that: The reducing organic alcohol is ethylene glycol and / or glycerol.
8. The preparation method according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 160-220° C., and the insulation time is 12-36 hours.
9. Use of the iridium-containing microcrystalline nanomaterial according to any one of claims 1 to 3 or the iridium-containing microcrystalline nanomaterial prepared by the preparation method according to any one of claims 4 to 8 as a catalyst in a proton exchange membrane water electrolyzer.
10. An anode of a proton exchange membrane water electrolyzer, characterized in that: It includes an anode substrate and an iridium-containing microcrystalline nanomaterial coated on the surface of the anode substrate; The iridium-containing microcrystalline nanomaterial is the iridium-containing microcrystalline nanomaterial according to any one of claims 1 to 3 or the iridium-containing microcrystalline nanomaterial prepared by the preparation method according to any one of claims 4 to 8.
Citation Information
Patent Citations
Method for preparing cluster-shaped IrO2 nano material based on hydrolysis method
CN113620358A
Porous iridium oxide nano material and preparation method and application thereof
CN115505951A
Iridium oxide cluster assembly catalyst for hydrogen production through acidic electrolysis of water and preparation method of iridium oxide cluster assembly catalyst
CN117285088A
Preparation method of high-activity iridium black catalyst
CN118595450A
Gallium oxide material loaded with iridium cluster as well as preparation method and application of gallium oxide material
CN119194505A
Cited By
Iridium-cluster-loaded strontium titanate as well as preparation method and application thereof
CN119506946A
Strontium titanate loaded with iridium clusters, and preparation method and application thereof
CN119506946B